Targeted and systematic cognitive freehand‐guided transperineal biopsy: is there still a role for systematic biopsy?. (19th May 2020) - Neale, Anoushka; Stroman, Luke; Kum, Francesca; Jabarkhyl, Dost; Di Benedetto, Antonina; Mehan, Nicholas; Rusere, Jonah; Chandra, Ashish; Challacombe, Ben; Cathcart, Paul; Dasgupta, Prokar; Elhage, Oussama; et al.
Abstract : Objectives: To assess whether targeted cognitive freehand‐assisted transperineal biopsies using a Precisionpoint TM device still require additional systematic biopsies to avoid missing clinically significant prostate cancer, and to investigate the benefit of a quadrant‐only biopsy approach to analyse whether a quadrant or extended target of the quadrant containing the target only would have been equivalent to systematic biopsy. Patients and Methods: Patients underwent combined systematic mapping and targeted transperineal prostate biopsies at a single institution. Biopsies were performed using the Precisionpoint device (Perineologic, Cumberland, MD, USA) under either local anaesthetic (58%, 163/282), i.v. sedation (12%, 34/282) or general anaesthetic (30%, 85/282). A mean (range) of 24 (5–42) systematic and 4.2 (1–11) target cores were obtained. Magnetic resonance imaging (MRI) scans were reported using the Likert scale. Clinically significant cancer was defined as Gleason 7 or above. Histopathological results were correlated with the presence of an MRI abnormality within a spatial quadrant and the other adjoining or non‐adjoining (opposite) quadrants. Histological concordance with radical prostatectomy specimens was analysed. Results: A total of 282 patients were included in this study. Their mean (range) age was 66.8 (36–80) years, median (range) prostate‐specific antigen level 7.4 (0.91–116) ng/mL and mean prostate volume 45.8 (13–150) mL. In this cohort, 82% of cases (230/282) were primary biopsies and 18% (52/282) were patients on surveillance. In all, 69% of biopsies (195/282) were identified to have clinically significant disease (Gleason ≥3 + 4). Any cancer (Gleason ≥3 + 3) was found in 84% (237/282) of patients. Of patients with clinically significant disease, the target biopsies alone picked up 88% (171/195), with systematic biopsy picking up the additional 12% (24/195) that the target biopsies missed. This altered with Likert score; 73% of Likert score 3 disease was detected by target biopsy, 92% of Likert score 4 and 100% of Likert score 5. Target biopsies with additional same‐quadrant‐only systematic cores picked up 75% (18/24) of significant cancer that was missed on target only, found in the same quadrant as the target. Conclusion: Systematic biopsy is still an important tool when evaluating all patients referred for prostate biopsy, but the need is decreased with increasing suspicion on MRI. Patients with very high suspicion of prostate cancer (Likert score 5) may not require systematic cores, unless representative surrounding biopsies are required for other specific treatments (e.g. focal therapy, or operative planning). More prospective studies are needed to evaluate this in full.